Overview of the SPARC tokamak. (October 2020) - Creely, A. J.; Greenwald, M. J.; Ballinger, S. B.; Brunner, D.; Canik, J.; Doody, J.; Fülöp, T.; Garnier, D. T.; Granetz, R.; Gray, T. K.; Holland, C.; Howard, N. T.; et al.
Abstract : The SPARC tokamak is a critical next step towards commercial fusion energy. SPARC is designed as a high-field ( $B_0 = 12.2$ T), compact ( $R_0 = 1.85$ m, $a = 0.57$ m), superconducting, D-T tokamak with the goal of producing fusion gain $Q>2$ from a magnetically confined fusion plasma for the first time. Currently under design, SPARC will continue the high-field path of the Alcator series of tokamaks, utilizing new magnets based on rare earth barium copper oxide high-temperature superconductors to achieve high performance in a compact device. The goal of $Q>2$ is achievable with conservative physics assumptions ( $H_{98, y2} = 0.7$ ) and, with the nominal assumption of $H_{98, y2} = 1$, SPARC is projected to attain $Q ≈ 11$ and $P_{fusion} ≈ 140$ MW. SPARC will therefore constitute a unique platform for burning plasma physics research with high density ( $\langle n_{e} \rangle ≈ 3 × 10^{20}\ m^{-3}$ ), high temperature ( $\langle T_e \rangle ≈ 7$ keV) and high power density ( $P_{fusion}/V_{plasma} ≈ 7\ MW\, m^{-3}$ ) relevant to fusion power plants. SPARC's place in the path to commercial fusion energy, its parameters and the current status of SPARC design work are presented. This work also describes the basis for global performance projections and summarizes some of the physics analysis that is presented in greater detail in the companion articles of this collection.